(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This paper explores the challenges of 'Policy Problem Structuring' and highlights the dilemmas faced by countries in South Asia. Here, the key purpose is to emphasize that in the process of problem structuring, the experiences of South Asian countries differ significantly from those of Western ones, which often frame social, and economic issues as ‘dilemmas’ in policy framing. The dilemmas are mainly three: how to select relevant policy values while determining the ethical principles and priorities, how to choose a policy model that can effectively address the identified issues, and lastly how to define and justify the idea of benefit. To illustrate this point, the paper emphasizes that a balanced approach using both post-positivism and interpretivism allows policy analysts to understand better the complexities of policy problem structuring and the significant dilemmas encountered primarily by South Asian nations.